PENGARUH PERBEDAAN JENIS KELAMIN TERHADAP INDEKS MASSA TUBUH PADA PASIEN SKIZOFRENIA DI RSU MADANI MEDAN TAHUN 2021 - OCTARI AULIATI; DEBBY MIRANI LUBIS (JURNAL ILMIAH KOHESI, 2023)
Schizophrenia is a severe mental disorder characterized by disturbances of thought, emotion, and behavior in the sufferer. Someone with schizophrenia is very at risk of being overweight, so that an increase in Body Mass Index (BMI) is related to the quality of life so that it can worsen the quality of life in people with schizophrenia. To determine the effect of gender differences on Body Mass Index in Schizophrenic patients at Madani Hospital Medan. Method: Analytical using cross sectional design. The number of samples in this study were 57 people using the Chi Square test. Based on the results of the analysis using the chi square test, there was no significant relationship between gender and body mass index with p value = 0.775 (p>0.05). This statistically shows that there is no significant relationship between gender and body mass index. There is no significant relationship between gender and body mass index in schizophrenic patients. Keywords: Gender, Body Mass Index, and Schizophrenia